The declaration of the victim of the gender violence crime: latest jurisprudential trends in Spain - Alicia González Monje (Revista Brasileira de Direito Processual Penal)
The declaration of the victim of the crime has been gaining prominence in the Spanish criminal process, to the point of becoming essential to enervate the presumption of innocence in those processes in which it is the only proof of charge. This circumstance has become even more relevant, even if possible, in crimes related to gender violence, characterized, on the one hand, by the special characteristics that converge on someone who, in addition to being a victim of the criminal act, is a witness to it and, on the other, due to the scarce body of evidence that the judge usually has in the criminal proceedings followed by such acts, as these are behaviours generally committed in the intimacy of the couple's relationship. The purpose of this work is to analyse the guiding parameters provided by the Spanish Supreme Court in the declaration of such victims. The traditional jurisprudential position will be examined and the expansion that these criteria have made in the recent ruling of the Supreme Court 119/2009, of March 6, will be critically assessed afterward, to determine the need or not for such expansion, as well as the incidence of its application in the processes followed by crimes related to gender violence.